2019
DOI: 10.1039/c9ra08045g
|View full text |Cite
|
Sign up to set email alerts
|

Flavin-mediated extracellular electron transfer in Gram-positive bacteria Bacillus cereus DIF1 and Rhodococcus ruber DIF2

Abstract: A flavin-mediated EET process was reported here in two new isolated electrochemically active Gram-positive bacterial strains DIF1 and DIF2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Microbial cell-to-electrode electron transfer by Synechocystis must therefore be facilitated by an alternative, i.e., non-pili-mediated, mechanism, either by direct transfer from some other cell surface electron transport proteins or by mediated-transfer via unknown redox-shuttles excreted into the extracellular environment/electrolyte ( Saper et al, 2018 ; Wenzel et al, 2018 ). Secreted flavins have been detected in cultures of Shewanella and other bacteria and are believed to play a role in EET by serving as soluble redox mediators ( Okamoto et al, 2013 ; Tian et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial cell-to-electrode electron transfer by Synechocystis must therefore be facilitated by an alternative, i.e., non-pili-mediated, mechanism, either by direct transfer from some other cell surface electron transport proteins or by mediated-transfer via unknown redox-shuttles excreted into the extracellular environment/electrolyte ( Saper et al, 2018 ; Wenzel et al, 2018 ). Secreted flavins have been detected in cultures of Shewanella and other bacteria and are believed to play a role in EET by serving as soluble redox mediators ( Okamoto et al, 2013 ; Tian et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, riboflavin can act as an electron shuttle to directly mediate electron transfer. On the other hand, riboflavin can act as a cofactor to improve the EET rate of other electron shuttles [ 26 ]. Therefore, Riboflavin concentration was detected.…”
Section: Resultsmentioning
confidence: 99%
“…These redox compounds can be a metabolite produced by the microorganism (e.g. flavins, phenazines, quinones) [62] , [63] , [64] or an artificial electron shuttle that can be added to the system (e.g. poly(MPC-co-VF), macrocyclic cobalt hexamines, osmium redox polymers) [57] , [65] , [66] .…”
Section: Indirect Electron Transfer In Gram-positive Bacteriamentioning
confidence: 99%
“…PTH1 to achieve EET [39] . But later on, it was demonstrated that Gram-positive bacteria can also produce redox mediators, such as humic acids, quinones and flavins [16] , [44] , [61] , [62] , [67] . For example, Lactococcus lactis cells can catalyse EET to an electrode by the excretion of soluble quinones as redox mediators [45] , while spore-forming bacteria belonging to Bacillus genus have the ability to excrete flavins [41] , [61] , [62] , [68] , [69] , [70] .…”
Section: Indirect Electron Transfer In Gram-positive Bacteriamentioning
confidence: 99%
See 1 more Smart Citation